City Park as an Adaptive Communal Place in COVID-19 Pandemic Era (Study Case: Merdeka Town Square) (International Journal of Architecture and Urbanism, 2025)
The covid-19 pandemic has forced people to isolate themselves at home and advised them not to leave the city. All public transportation has stopped working to avoid commuting. As a human, we require relaxation to have a calmer and clearer mind. The health protocol advised safe outdoor activities (with no air conditioning to reduce the risk of exposure and transmission of the virus. Social distancing, avoiding crowds and poorly ventilated indoor spaces can be done by doing activities in the central park (such as the town square). This town square could be an excellent decision to fulfil the need for tourism, completed by some adaptive designs to deal with this pandemic situation. Unfortunately, the government closed this facility and led some citizens to fulfil their needs by going to the mall quite often than before. People gathered into the crowd and some indoor activities, made the mall as their new preferred tourism destination. Therefore, this morphological research aims to reveal the importance of Merdeka Town Square as an adaptive communal place in the pandemic situation, using an activity approach (place-centered mapping). Through this research and some design recommendations, we hope to present an educational discussion about an adaptive communal space to the citizens and government